Long-term outcomes and immune profiling in children with multisystem inflammatory syndrome (MIS-C) - Jaxybayeva, Indira; Boranbayeva, Riza; Bulegenova, Minira; Urazalieva, Nataliya; Gerein, Valentin; Manzhuova, Lyazat (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Existing follow-up data after MIS-C is limited. Purpose of the study: to investigate the long-term consequences in children who have undergone MIS-C.Methods: The retrospective study included 93 children. The identified changes were divided into the following periods: occurred within first 6 months, 1 year, 2 years, and more than 2 years after MIS-C. Besides, 31 children underwent prospective immunophenotyping of peripheral blood and the determination of cytokines during the acute period of the disease and after discharge.Results: Outpatient monitoring events included pneumonia (9.6%), somatic disorder syndrome (11.8%), visual impairment (7.5%), joint damage (6.6%), weight changes (2.2%), and MIS-C recurrence (2.2%). A study of the cardiovascular system showed a statistically significant decrease in the frequency of the right and left heart dilatation, left ventricular dysfunction, pericarditis, pulmonary arterial hypertension, coronaritis, mitral regurgitation. But at the same time an increase in pulmonary and tricuspid valve regurgitation and arrhythmias compared with the acute period was detected. Most of the changes took place within first year of observation.Immune profiling showed reconstitution of CD3, CD4 T-lymphocytes, NK-cells, maintenance of a high relative value of CD8, reduction of CD19+ B-cells, expression of CD3-HLA-DR+, CD25, CD279, CD95.Conclusions: After the history of MIS-C, children in the long-term follow-up had various somatic disorders and disease recurrence. Most patients (64.1%) showed subclinical signs of myocardial involvement within first year of observation. Low expression of CD95 may justify an certain role in the pathogenesis of the disease.